Genomic epidemiology and characterization of Staphylococcus aureus isolates from raw milk in Jilin, China: evidence of contamination with optrA-positive, cfrA-positive, and poxtA-positive strains and human–livestock transmission - Qianhong Liu; Qianhong Liu; Pengming Ma; Qiaoyi Gu; Wen Yang; Chunhua Li (Frontiers in Microbiology)
Jilin province is the primary region for dairy cow and milk production in China. However, there are few reports on the genetic characteristics, antibiotic resistance, and prevalence of Staphylococcus aureus (S. aureus) in raw milk. Between 2021 and 2022, researchers identified 214 S. aureus strains, with a prevalence rate of 42.8% in cattle farms across Jilin province. Among the 214 strains, 22 isolates of methicillin-resistant Staphylococcus aureus (MRSA) were identified, with 13 exhibiting prevalent antibiotic resistance. Penicillin exhibited the highest resistance rate (145/214, 67.76%). The profiles of drug resistance, pathogenicity, genetic traits, and biofilm formation were examined through whole genome sequencing (WGS) of 44 isolates, comprising 22 MRSA strains and 22 methicillin-sensitive Staphylococcus aureus (MSSA) strains. Of the 44 isolates, 25 (56.82%) exhibited multiple resistance, while 31 (70.45%) demonstrated drug resistance characteristics. We identified 12 distinct types of drug resistance genes, including those associated with tetracycline, quaternary ammonium salt disinfection, and β-lactam. Six strains were found to carry genes conferring resistance to linezolid. The Aur and hlgA/B/C virulence genes were identified in at least 90% of the strains, with ST9-t899 emerging as the predominant type. Human–livestock transmission may be present, as indicated by the single-nucleotide polymorphism (SNP) and WGS data. The isolates also exhibited increased resistance. Moreover, strong biofilm formation was observed among the MRSA strains compared to the MSSA strains. The isolates exhibited multi-drug resistance, a broad spectrum of drug resistance, and various drug resistance phenotypes. CC398 and CC9 demonstrated potential for human-to-livestock transmission, as evidenced by the identification of 22 CC9 and 15 CC15 strains among the 44 isolates. OptrA, cfrA, and poxtA genes were identified in five, seven, and one strains, respectively, indicating contamination within the population. Given that raw milk is a fundamental food source, it is essential to monitor the molecular characteristics and antimicrobial resistance (AMR) of S. aureus to ensure food safety and hygiene. From a One Health perspective, controlling antimicrobial resistance (AMR) is crucial as it can be transmitted from food-producing animals to humans, thus impacting public health.